Ogroženost za padce v terciarni bolnišnici - Klančnik-Gruden, Maja (Obzornik zdravstvene nege, 2018)
Introduction: The purpose of the study was to determine the risk for falls in adult patients in acute care setting and differences in risk between groups with respect to gender, age, clinical setting (clinic) and medical specialty, as well as the category of nursing care complexity. Methods: A quantitative study - a cross-sectional observational study was used. Adult patients hospitalized in University Medical Centre Ljubljana were included in the sample (n = 1,361). The instrument was developed for collecting data, where the risk for falls was evaluated with the Morse Fall Scale. The data were collected from October to November 2015. In addition to basic descriptive statistics, the Mann-Whitney test, the ANOVA test and Pearson correlation test were also used. Results: The study showed that in acute care given in a Slovenian tertiary hospital, 69.1 % (n = 940) of patients were at moderate to severe risk for falls, of which 28.0 % (n = 381) were at severe risk. The risk for falls was positively related to age (r = 0.462, p < 0.001). It also differed according to department (F=29.210, p < 0.001), according to the medicine specialty (Z = %5.660, p < 0.001) and according to the category of nursing complexity of care (F = 125.464, p < 0.001). Discussion and conclusion: Older people, people in higher categories of nursing care complexity and medical units' patients have a significantly higher risk for falls than others. Routine assessment of risk for falls, planning and implementation of falls prevention measures are the basis for reducing falls.
Keywords: acute care; akutna zdravstvena oskrba; dejavniki tveganja; falls; Morse Falls Scale; Morsejina lestvica padcev; padci; risk factors; safety incidents; varnostni zapleti